MANAGEMENT PROBLEMS OF ENTERPRISES IN WORLD CRISIS (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The article is dealt with, that there are plenty of risks in any industry. And managers have to solve different problems every day to stay relevant and profitable. It is a well-known fact that modern entrepreneurs want to become harmonious and successful. It is believed that successful business is the art of managing limited resources in conditions of constant risk and unlimited opportunities. Management of companies in any industry has its own nuances. For example, food enterprises. Managers of this industry must run their business and on the other hand there is strict liability because these enterprises ensured food security - one of the most important functions of the state. Risk is known to be a potential problem that can drive development or destroy a business. Thus, most scientists identify risks, like economic, political, reputational risks, the threat of losing competitive advantage, environmental, price, technical, investment, currency, legal and others. Therefore, it is extremely important for any entrepreneur to clearly identify all the risks associated with doing business to implement an effective business management system. Among the most significant risks, in 2020, entrepreneurs identify quarantine caused by the COVID 2019 virus (coronavirus disease). Overcoming the crisis in 2020 is mainly related to the fight against the pandemic and the support of health care facilities. However, other industries, especially the food industry, tourism, hotel, restaurant business, etc., also need support. An important direction in solving the problem should also be given to food security, improving the quality of food, quality of services, focus on the environment, which will address the effects of the crisis, increase GDP, and, consequently, improve welfare, emigration and unemployment, will improve life expectancy.
Keywords: crisis management, food quality, enterprise management, business risks, food industry, food security